Analisis Akuntabilitas, Transparansi, dan Partisipasi Masyarakat dalam Pengelolaan Keuangan Nagari - Alvionita, Revi; Mustika, Rasyidah; Andriani, Wiwik (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2023)
This research aims to determine accountability, transparency and community participation in managing nagari finances in Nagari Tanjuang Labuah, Sumpur Kudus District, Sijunjung Regency. The type of research is qualitative research. The data used in this research are primary data and secondary data. Data collection techniques through interviews, observation and documentation. The indicators used to measure accountability, transparency and community participation in nagari financial management are based on Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Financial Management. The data analysis techniques used are data reduction, data presentation, drawing conclusions. The results of the research show that accountability and transparency in managing nagari finances in Nagari Tanjuang Labuah have not been fully implemented in accordance with Minister of Home Affairs Regulation Number 20 of 2018. Meanwhile, community participation in managing nagari finances in Nagari Tanjuang Labuah has been implemented in accordance with Minister of Home Affairs Regulation Number 20 2018